2017
DOI: 10.1590/1517-869220172306171864
|View full text |Cite
|
Sign up to set email alerts
|

Association of Actn3 R577x and Ace I/D Polymorphisms in Brazilians Wrestlers

Abstract: Introduction: By associating genetics and sport, it is possible to identify subjects with greater capacity to adapt to training, and lower chances of injury. Objective: The investigation evaluated the genotypic and allelic distribution of ACTN3 R577X and ACE I/D polymorphisms in Brazilian high-performance athletes in wrestling and percussion combat sports. Methods: The study included 37 male athletes ranked from first to third place in world scenarios, divided into two groups: wrestling (23 wrestlers, being 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The DD and ID individuals showed an increased potential for improved sporting performance. These findings are in agreement with other reports (Gineviciene et al, 2016;Ribas et al, 2017;Weyerstra et al, 2017;Jacob et al, 2018) and can be justified by the high degree of heterogeneity found in the Brazilian population (Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The DD and ID individuals showed an increased potential for improved sporting performance. These findings are in agreement with other reports (Gineviciene et al, 2016;Ribas et al, 2017;Weyerstra et al, 2017;Jacob et al, 2018) and can be justified by the high degree of heterogeneity found in the Brazilian population (Santos et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The authors reported that the DD genotype was more predominant in wrestlers compared with controls (45.7 vs. 32.2%, respectively). This study also suggested that the more predisposed to fight sports are individuals with ACE gene alleles related to strength and muscle power (Ribas et al, 2017). Thus, based on the role of ACE I/D polymorphism in anaerobic power, strength, and muscle power, we speculate that determining ACE genomic status could facilitate identifying athletes with optimal performance in distinct soccer positions.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, the endurance athletes had a similar genotype distribution for RR and RX (see Table 3) but important differences were obtained on both the XX genotype (20% endurance vs. 7.4% in the strength-group) and the allelic frequency (R = 55%, X = 45%). This behaviour of the data is in accordance with previous reports in athletes trained for strength, power or high-intensity short-rest efforts (Nir Eynon et al, 2013;Lammi, Tharabenjasin, Pabalan, & Jarjanazi, 2019;Ribas et al, 2017). For example, Eynon et al (Nir Eynon et al, 2013) showed a genotype distribution on elite and national-level strength/power-athletes from Spain (n = 119, RR: 31%, RX: 55%, and XX: 13%), Poland (n = 178, RR: 40%, RX: 52%, and XX: 8%) and Russia (n = 82, RR: 40%, RX: 48%, and XX: 12%) that were similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…The ACE I/D was identified as the absence (deletion or D allele) or presence (insertion and I allele) of 287 base pairs in intron 16 of the gene (Ribas et al, 2017). This was confirmed by the presence of a 490 bp segment for alleles II, whilst a 190 pb fragment was detected for alleles DD.…”
Section: Ace I/d (Rs1799752) Genotypingmentioning
confidence: 86%
“…Owing to the diverse array of desirable physical attributes in sport, several polymorphisms within the human genome have previously been highlighted. For example, the angiotensin-converting enzyme ( ACE ) and alpha-actinin-3 ( ACTN3 ) genes have both been linked with elite levels of athletic performance in endurance and/or strength/power dominant sports; including long distance running and swimming, road cycling, rowing, cross-country skiing, triathlons, sprinting, volleyball, track and field jumping and throwing, weightlifting, ice hockey, wrestling, and figure skating [ 16 , 17 , 18 , 19 , 20 ]. In addition, specific homozygous genotypes in the peroxisome proliferator-activated receptor gamma co-activator 1-alpha ( PPARGC1A ) gene and the beta-adrenergic receptors 1/2/3 ( ADRB 1/2/3 ) have been linked with higher maximal oxygen uptake (VO 2 max), better endurance performance and more favourable body mass index in long-distance runners, long-distance swimmers road cyclists, cross-country skiers, triathletes, sprinters, sprint swimmers, weight and power lifters, track and field jumpers and throwers, boxers, and kayakers [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%